Enhancing heat transfer performance of automotive car radiator using camphor nanoparticles: experimental study with bibliometric analysis - Kolakoti, Aditya; Setiyo, Muji; Husaeni, Dwi Novia Al; Nandiyanto, Asep Bayu Dani (Universitas Negeri Padang, 2023)
In this study, an attempt was made to investigate the heat transfer performance of a four-wheeler automotive radiator using a novel coolant system. To support this study, we also added bibliometric analysis to show the importance of this study. In the experiments, camphor nanoparticles (sizes of 511 nm) with various loadings (i.e. 2, 4, 6, and 8%) were mixed with deionized water (DW) to create a coolant. The experiments were conducted at different heat convection processes (i.e. 0.5, 1.45, and 3.7 m/s). The significant heat transfer performance parameters, such as Reynolds number (Re), Nusselt number (Nu), overall heat transfer coefficient (U), and heat transfer rate (Q), were examined. The Fourier Transform Infrared results revealed the presence of significant functional groups in the coolant system. camphor nanoparticles dispersed in DW were stable for more than 8 hours. At 70 ᵒC, the novel coolant (2% camphor nanoparticles in DW) exhibits better Re, Nu, U, and Q than that using pure DW or other loadings of nanoparticles (e.g. 4, 6, and 8%). The high percentage of camphor nanoparticles in DW restricts the fluid flow, resulting in a drop in overall heat transfer performance. Finally, low-cost, easily available, and eco-friendly camphor nanoparticles (2%) are suggested as a better choice in lieu of high-cost metallic and non-metallic nanoparticles as an additive in the coolant system.